Bidirectional and context-dependent changes in theta and gamma oscillatory brain activity in noradrenergic cell-specific Hypocretin/Orexin receptor 1-KO mice. Issue 1 (December 2018) - Li, Sha; Franken, Paul; Vassalli, Anne
Abstract Noradrenaline (NA) and hypocretins/orexins (HCRT), and their receptors, dynamically modulate the circuits that configure behavioral states, and their associated oscillatory activities. Salient stimuli activate spiking of locus coeruleus noradrenergic (NALC ) cells, inducing NA release and brain-wide noradrenergic signalling, thus resetting network activity, and mediating an orienting response. Hypothalamic HCRT neurons provide one of the densest input to NALC cells. To functionally address the HCRT-to-NA connection, we selectively disrupted theHcrtr1 gene in NA neurons, and analyzed resulting (Hcrtr1 Dbh -CKO ) mice', and their control littermates' electrocortical response in several contexts of enhanced arousal. Under enforced wakefulness (EW), or after cage change (CC), Hcrtr1 Dbh -CKO mice exhibited a weakened ability to lower infra-θ frequencies (1–7 Hz), and mount a robust, narrow-bandwidth, high-frequency θ rhythm ( 8.5 Hz). A fast-γ (55–80 Hz) response, whose dynamics closely parallelled θ, also diminished, while β/slow-γ activity (15–45 Hz) increased. Furthermore, EW-associated locomotion was lower. Surprisingly, nestbuilding-associated wakefulness, inversely, featured enhanced θ and fast-γ activities. Thus HCRT-to-NA signalling may fine-tune arousal, up in alarming conditions, and down during self-motivated, goal-driven behaviors. Lastly, slow-wave-sleep following EW and CC, but not nestbuilding, was severely deficient in slow-δ waves (0.75–2.25 Hz), suggesting that HCRT-to-NA signalling regulates the slow-δ rebound characterizing sleep after stress-associated arousal.